Why axis inversion? Optimizing interactions between users, interfaces, and visual displays in 3D environments - Corbett, Jennifer E.; Munneke, Jaap (Cognitive research: principles and implications, 2025)
From video games to laparoscopic surgeries, differences in users’ abilities to adapt to new control schemes can have significant, even deadly impacts on performance. Starting with the question of why some video game players invert the y-axis on their console controllers, this work aims to provide a foundation for future investigations of how control schemes can significantly impact performance. We argue that fragmented research across disciplines hinders a unified understanding of how the spatial relationships between users, interfaces, and visual displays affect performance. Therefore, we begin with a multidisciplinary literature synthesis, clarifying existing findings, and identifying methodological inconsistencies that contribute to conflicting results. We then explore the relationship between key behavioral and cognitive factors and y-axis inversion preference in a group of experienced 3rd person gamers. Based on these preliminary results, we propose a “general purpose” framework to systematically investigate how control inversion and visual input influence perception and performance across various movement goals. We demonstrate how this framework can be used to evaluate performance in the context of a common and challenging laparoscopic procedure, and how it can be generalized to assess and predict sensorimotor compatibility effects across a wide variety of real-world situations.